Takut Akan Tuhan Sebagai Dasar Hidup Kaum Muda: Telaah Amsal 1:7 dalam Konteks Milenial dan Gen Z: I. Latar Bekalang Kitab Amsal - Krisna Sianturi; Gregorius Tri Wardoyo; Benny Phang Khong Wing (Seri Filsafat Teologi, 2025)
Millennials and Gen Z live in an era characterized by technological advances, rapid information flow, and shifting social and spiritual values. In the midst of this reality, they face serious challenges in shaping a meaningful life that is morally and spiritually rooted. Moral relativism, individualism, and secularism have become dominant characteristics that erode submission to divine authority, and cause many young people to experience value confusion, spiritual emptiness, and a crisis of meaning in life. In this context, Proverbs 1:7 "The fear of the LORD is the beginning of knowledge" becomes an important foundation in building a wise and responsible life. This article aims to exegetically and theologically examine the meaning of "fear of the Lord" in the light of Proverbs 1:7, and relate it to the spiritual and ethical challenges facing the Millennial and Gen Z generations. The research shows that the "fear of the Lord" is not simply fear in a negative sense, but rather an attitude of reverence, submission, and awareness of God's presence and authority in all aspects of life. This attitude is the foundation of true wisdom, which guides young people to live with clear direction, solid values, and rooted spirituality. With this foundation, young people are encouraged to not only survive the flow of the times but also become agents of transformation who bring light during a dark world. The role of faith communities is crucial in instilling this value so that young people grow into spiritually and ethically strong individuals.